Methodology for the assessment of poor-data water resources - Navarro-Farfán,María del Mar; García-Romero,Liliana; Martínez-Cinco,Marco A.; Domínguez-Sánchez,Constantino; Sánchez-Quispe,Sonia Tatiana (PeerJ, 2024)
Surface hydrologic modeling becomes a problem when insufficient spatial and temporal information is available. It is common to have useful modeling periods of less than 15 years. The purpose of this work is to develop a methodology that allows the selection of meteorological and hydrometric stations that are suitable for modeling when information is scarce in the area. Based on the scarcity of data, a series of statistical tests are proposed to eliminate stations according to a decision-making process. Although the number of stations decreases drastically, the information used is reliable and of adequate quality, ensuring less uncertainty in the surface simulation models. Individual basin modeling can be carried out considering the poor data. The transfer of parameters can be applied through the nesting of basins to have information distributed over an extensive area. Therefore, temporally and spatially extended modeling can be achieved with information that preserves statistical parameters over time. If data management and validation is performed, the modeled watersheds are well represented; if this is not done, only 26% to 50% of the runoff is represented.
Keywords: Poor-data; Methodology; Surface modeling; Data analysis; Nested basins